Preparation method and application of multilayer graphite coated aluminum nitride ceramic powder
A multilayer graphite-coated aluminum nitride ceramic powder is prepared using tannic acid and graphene oxide, addressing the trade-off in thermal conductivity and wave absorption, achieving high performance and flexibility in wave-absorbing materials.
Patent Information
- Application Number
- CN202411363261.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Existing thermal conductive wave absorbing materials face challenges in achieving both high thermal conductivity and strong electromagnetic wave absorption due to the trade-off between filler addition and material flexibility, with conventional methods using toxic organic modifiers and limited filler ratios.
A method involving the chemical modification of aluminum nitride with tannic acid, followed by coating with graphene oxide and high-temperature reduction to form a multilayer graphite-coated ceramic powder, combined with an organic crosslinking agent to create a heat-conducting and wave-absorbing gasket.
The method achieves high thermal conductivity and effective electromagnetic wave absorption while maintaining material flexibility, reducing environmental impact through the use of non-toxic tannic acid and allowing for higher filler ratios.
Smart Images

Figure CN119118681A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic thermal management materials, and specifically relates to a preparation method and application of a multilayer graphite-coated aluminum nitride ceramic powder. Background Art
[0002] With the vigorous development of 5G technology, the integration and operating power of electronic components are constantly increasing, and a large amount of waste heat is generated during operation, which seriously affects the reliability of electronic equipment. Due to the small internal space and poor air circulation of electronic equipment, waste heat is mainly dissipated by heat conduction. Due to the large contact thermal resistance at the device interface, it is difficult for waste heat to be dissipated to the external environment in a timely manner. Therefore, thermal interface materials need to be filled at the interfaces of high-power chips, CPU processors and other devices to improve the heat dissipation efficiency and prevent electronic equipment from overheating. At the same time, as the operating frequency of electronic equipment becomes higher and higher, the problem of electromagnetic pollution has become more serious. Electronic components working in a closed environment will radiate electromagnetic waves to the outside world, causing electromagnetic interference to surrounding electronic components. It is necessary to mount absorbing materials on their surface to solve this problem.
[0003] At present, the main research and development idea of thermal conductive wave absorbing materials is to add high thermal conductive fillers and wave absorbers to the polymer matrix at the same time to achieve the dual functions of thermal conduction and electromagnetic wave absorption. However, the key challenge is that it is often difficult to take into account both efficient thermal conductivity and strong electromagnetic wave absorption. For example, the thermal conductivity of the thermal conductive gasket produced by Laird can reach 7.5W / mK (TflexTMHD90000), while the thermal conductivity of the thermal conductive wave absorbing gasket with the best performance is only 4W / mK (CoolZorbTM500). The main reason is that there is a maximum limit to the addition of functional fillers in the polymer matrix, and there is a problem of trade-off between thermal conductivity and wave absorbing performance as the proportion of filler addition changes. In addition, excessive filler addition will also sacrifice the flexibility of the gasket material.
[0004] Therefore, a preparation method of multilayer graphite-coated aluminum nitride ceramic powder and its application are urgently needed. Summary of the invention
[0005] In order to solve the defects of the prior art, the present invention provides a preparation method and application of multi-layer graphite-coated aluminum nitride ceramic powder.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] The first object of the present invention is to provide a method for preparing a multilayer graphite-coated aluminum nitride ceramic powder, comprising the following steps:
[0008] S11, chemically modifying the surface of aluminum nitride by using tannic acid to prepare tannic acid-modified aluminum nitride powder with surface activity, and adding the powder into deionized water for ultrasonic dispersion to obtain a tannic acid-modified aluminum nitride suspension;
[0009] S12, coating the surface of modified aluminum nitride with graphene oxide, adding graphene oxide to a deionized water solution for ultrasonic dispersion to obtain a graphene oxide dispersion, dripping the graphene oxide dispersion into the nicotinic acid-modified aluminum nitride suspension obtained in step S11 while stirring, centrifuging after the dripping, and drying to obtain composite particles of composite particles of graphene oxide-coated aluminum nitride ceramic powder;
[0010] S13, placing the composite particles obtained in step S12 in a high-temperature furnace for high-temperature reduction in a protective gas environment, reducing the graphene oxide on the surface into graphene and carbonizing the tannic acid into amorphous carbon by high temperature, and obtaining a multilayer graphite-coated aluminum nitride ceramic powder.
[0011] Preferably, the specific operation method of chemically modifying the aluminum nitride surface with tannic acid in S11 is: dissolving tannic acid in anhydrous ethanol, adding aluminum nitride powder and deionized water, ultrasonically dispersing, and then stirring and heating in a water bath environment;
[0012] Among them, the mass ratio of the aluminum nitride powder to tannic acid is 1:0.4-0.5, the mass volume ratio of the aluminum nitride powder, anhydrous ethanol and deionized water is 1g:12-13mL:0.4g; the ultrasonic dispersion time is 30-60min; the water bath temperature is 75-80°C, the stirring speed is 500-600rpm, and the stirring and heating time in the water bath environment is 210-300min.
[0013] Preferably, in step S12, the mass ratio of modified aluminum nitride to graphene oxide is 20 to 50:1;
[0014] The ultrasonic dispersion time of the graphene oxide in the deionized water solution is 30 to 60 minutes; the stirring speed is 400 to 600 rpm; the centrifugal parameter is 4000 rpm for 4 minutes, repeated four times; and the drying method is freeze drying for 24 to 48 hours.
[0015] Preferably, in step S13, the graphene oxide-coated aluminum nitride ceramic powder is reduced at a high temperature of 800 to 850° C. for 4.5 to 5.5 hours in a nitrogen environment, and then cooled to room temperature along with the furnace.
[0016] The second object of the present invention is to provide a method for preparing a heat-conducting and wave-absorbing gasket, comprising the following steps:
[0017] S21, grading the multi-layer graphite-coated aluminum nitride ceramic powder and the aluminum nitride powder to obtain a multi-layer graphite-coated aluminum nitride graded powder;
[0018] S22, adding an organic crosslinking agent and a curing agent to the multi-layer graphite-coated aluminum nitride graded powder, mechanically stirring, vacuuming and removing bubbles, and then standing to obtain a multi-layer graphite-coated aluminum nitride thermal conductive and wave absorbing slurry;
[0019] S23, using a tablet press to press the multi-layer graphite-coated aluminum nitride thermally conductive and absorbing slurry into a uniform sheet, and curing it in a high temperature environment to obtain a multi-layer graphite-coated aluminum nitride thermally conductive and absorbing gasket.
[0020] Preferably, in step S21, the particle size of the aluminum nitride powder is 30-35 μm.
[0021] Preferably, in step S21, the gradation mass ratio of the multilayer graphite-coated aluminum nitride ceramic powder to the aluminum nitride powder is 1:0.5-2.
[0022] Preferably, the organic cross-linking agent in step S22 comprises maleic anhydride and hydroxyl-terminated polybutadiene, and the mass ratio of maleic anhydride to hydroxyl-terminated polybutadiene is 1:0.5;
[0023] The curing agent is dodecyltrimethylsilane, and the content of the curing agent is 0.5% of the total mass of the multi-layer graphite-coated aluminum nitride thermal conductive wave absorbing slurry.
[0024] Preferably, in step S22, the mass ratio of the multilayer graphite-coated aluminum nitride graded powder to the organic cross-linking agent is 1:0.2-0.08.
[0025] Preferably, in step S23, the multi-layer graphite-coated aluminum nitride heat-conducting and wave-absorbing gasket is pressed to a thickness of 1 mm to 3 mm, the curing temperature is 120° C., and the curing time is 2 to 3 hours.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention uses tannic acid as a surface modifier for aluminum nitride. Traditional organic modifiers are mostly small molecule organic coupling agents with amine groups, which are toxic and cannot be degraded by the environment. They will cause harm to the environment during the research and production process, and waste liquid treatment will generate additional costs. Using tannic acid as a coupling agent can meet the green and pollution-free production requirements and reduce the costs generated by waste liquid treatment.
[0028] Tannic acid reacts with aluminum hydroxide produced by hydrolysis on the surface of aluminum nitride powder to coat the surface of aluminum nitride powder with carboxyl and carbonyl groups. The presence of carboxyl and carbonyl groups improves the wettability of aluminum nitride powder with deionized water, and it can be better dispersed in deionized water; at the same time, the carbonyl and carboxyl groups on the surface of aluminum nitride can form hydrogen bonds with the carboxyl and carbonyl groups on graphene oxide to coat graphene on the surface of aluminum nitride powder. The modified waste liquid only contains alcohol, deionized water and tannic acid, which reduces the treatment requirements of experimental waste liquid and reduces environmental pollution.
[0029] The present invention uses tannic acid as a surface modifier of aluminum nitride to adsorb graphene oxide and coat it on the surface of aluminum nitride, and then carbonizes the tannic acid on the surface of aluminum nitride through high-temperature reduction to form an amorphous carbon layer. The amorphous carbon layer has the characteristics of large specific surface area and many pores, and is an ideal material for a wave-absorbing shell layer. Forming an amorphous carbon layer between graphene and aluminum nitride can significantly improve the wave-absorbing performance of the material, so that high thermal conductivity and wave-absorbing performance can be achieved by adjusting the thickness of the graphene and amorphous carbon layers.
[0030] The present invention uses maleic anhydride and terminal hydroxyl polybutadiene as organic crosslinking agents, which can achieve extremely high thermal conductive filler ratio and excellent hardness and flexibility. The filler ratio limit of inorganic thermal conductive fillers in conventional organic gaskets is between 80% and 90%. The present invention can make the gasket have good flexibility and low hardness when the filler ratio reaches 92%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 a. Figure 1 b is a TEM image of the multilayer graphite-coated aluminum nitride ceramic powder of the present invention at 500nm and 10nm;
[0032] Figure 2 This is a SEM picture of the multi-layer graphite-coated aluminum nitride ceramic powder in the present invention.
[0033] Figure 3 This is a test diagram of the microwave absorption performance of the multi-layer graphite-coated aluminum nitride ceramic powder in Experimental Examples 1-3 of the present invention; Figure 3 Figures a, b, and c are electromagnetic wave reflection loss diagrams of Example 1, Example 2, and Example 3, respectively. Figure 3 Figures d, e, and f are the three-dimensional wave absorption mapping images of Example 1, Example 2, and Example 3, respectively;
[0034] Figure 4 These are the test results of thermal conductivity of the heat-conductive and wave-absorbing gaskets in Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0035] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0036] Example 1
[0037] This embodiment provides a method for preparing multi-layer graphite-wrapped aluminum nitride ceramic powder, the steps of which are as follows:
[0038] S11. Chemically modify the aluminum nitride surface to obtain a tannic acid-modified aluminum nitride suspension. (1) Add 6 g of tannic acid (AR analytical grade) to 200 mL of anhydrous ethanol and stir until the tannic acid is completely dissolved. Add 15 g of aluminum nitride powder with a particle size of 2 microns to the prepared tannic acid ethanol solution, and then add 6 g of deionized water. (2) Place the suspension system in a stirring water bath for heating and modification, place the modified suspension in a centrifuge for centrifugal separation, add the modified and cleaned aluminum nitride powder to deionized water and disperse in an ultrasonic dispersion environment to obtain a tannic acid-modified aluminum nitride suspension.
[0039] S12, coating graphene oxide on the surface of modified aluminum nitride to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder. (1) Add 0.75g of single-layer graphene oxide to 200mL of deionized water and disperse it ultrasonically for 1h to obtain a graphene oxide dispersion; (2) Add the graphene oxide dispersion dropwise into the tannic acid modified aluminum nitride suspension and place the mixed solution in a centrifuge for centrifugal separation. Place the precipitate in a freeze dryer and freeze-dry for 24h to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder.
[0040] S13, reducing the composite particles at high temperature to obtain multi-layer graphite-coated aluminum nitride ceramic powder (such as Figure 1 , 2 As shown), graphene oxide coated aluminum nitride ceramic powder is placed in a tube furnace and reduced under a nitrogen atmosphere.
[0041] This embodiment also provides a method for preparing a heat-conducting and wave-absorbing gasket, and the steps are as follows:
[0042] S21, multilayer graphite coated aluminum nitride ceramic powder and aluminum nitride powder are graded to obtain multilayer graphite coated aluminum nitride graded powder. (1) The aluminum nitride particle size used for grading is 30 microns; (2) The mass ratio of the grading is 1:1.1 for the multilayer graphite coated aluminum nitride and the aluminum nitride.
[0043] S22, adding an organic crosslinking agent and a curing agent to the graded powder of multilayer graphite coated aluminum nitride, mechanically stirring, vacuuming and removing bubbles, and then standing to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry. (1) Maleic anhydride and terminal hydroxyl polybutadiene are mixed in a mass ratio of 2:1 to obtain an organic crosslinking agent; (2) 13.8g of graded aluminum nitride powder and 1.2g of organic crosslinking agent are added to a mixing tank, and then 0.75g of dodecyltrimethylsilane is added as a curing agent, and the mixture is placed in a mixer and mixed under vacuum to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry.
[0044] S23, using a tablet press to press the multi-layer graphite-coated aluminum nitride thermally conductive and absorbing slurry into a uniform sheet, and curing it in a high temperature environment to obtain a multi-layer graphite-coated aluminum nitride thermally conductive and absorbing gasket.
[0045] The basic wave absorption performance of the multilayer graphite-coated aluminum nitride ceramic powder obtained on this basis is: RLmin = -56.17dB, and the wave absorption bandwidth is 5.2GHz (such as Figure 3 The thermal conductivity of the gasket is 5.54W / mK (as shown). Figure 4 shown).
[0046] Example 2
[0047] This embodiment provides a method for preparing multi-layer graphite-wrapped aluminum nitride ceramic powder, the steps of which are as follows:
[0048] S11. Chemically modify the aluminum nitride surface to obtain a tannic acid-modified aluminum nitride suspension. (1) Add 4 g of tannic acid (AR analytical grade) to 200 mL of anhydrous ethanol and stir until the tannic acid is completely dissolved. Add 15 g of aluminum nitride powder with a particle size of 2 microns to the prepared tannic acid ethanol solution, and then add 6 g of deionized water. (2) Place the suspension system in a stirring water bath for heating and modification, place the modified suspension in a centrifuge for centrifugal separation, add the modified and cleaned aluminum nitride powder to deionized water and disperse in an ultrasonic dispersion environment to obtain a tannic acid-modified aluminum nitride suspension.
[0049] S12. Coating graphene oxide on the surface of modified aluminum nitride to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder. (1) Add 0.375g of single-layer graphene oxide to 200mL of deionized water and disperse it ultrasonically for 1h to obtain a graphene oxide dispersion; (2) Add the graphene oxide dispersion dropwise into the tannic acid modified aluminum nitride suspension and place the mixed solution in a centrifuge for centrifugal separation. Place the precipitated part in a freeze dryer and freeze-dry for 24h to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder.
[0050] S13, reducing the composite particles at high temperature to obtain multilayer graphite-coated aluminum nitride ceramic powder, and placing the graphene oxide-coated aluminum nitride ceramic powder in a tubular furnace for reduction under a nitrogen atmosphere.
[0051] This embodiment also provides a method for preparing a heat-conducting and wave-absorbing gasket, and the steps are as follows:
[0052] S21, multilayer graphite coated aluminum nitride ceramic powder and aluminum nitride powder are graded to obtain multilayer graphite coated aluminum nitride graded powder. (1) The aluminum nitride particle size used for grading is 30 microns; (2) The mass ratio of the grading is 1:1.1 for the multilayer graphite coated aluminum nitride and the aluminum nitride.
[0053] S22, adding an organic crosslinking agent and a curing agent to the graded powder of multilayer graphite coated aluminum nitride, mechanically stirring, vacuuming and removing bubbles, and then standing to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry. (1) Maleic anhydride and terminal hydroxyl polybutadiene are mixed in a mass ratio of 2:1 to obtain an organic crosslinking agent; (2) 13.8g of graded aluminum nitride powder and 1.2g of organic crosslinking agent are added to a mixing tank, and then 0.75g of dodecyltrimethylsilane is added as a curing agent, and the mixture is placed in a mixer and mixed under vacuum to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry.
[0054] S23, using a tablet press to press the multi-layer graphite-coated aluminum nitride thermally conductive and absorbing slurry into a uniform sheet, and curing it in a high temperature environment to obtain a multi-layer graphite-coated aluminum nitride thermally conductive and absorbing gasket.
[0055] The basic wave absorption performance of the multilayer graphite-coated aluminum nitride ceramic powder obtained on this basis is: RLmin = -27.53dB, and the wave absorption bandwidth is 3.94GHz (such as Figure 3 The thermal conductivity of the gasket is 5.43W / mK (as shown). Figure 4 shown).
[0056] Example 3
[0057] This embodiment provides a method for preparing multi-layer graphite-wrapped aluminum nitride ceramic powder, the steps of which are as follows:
[0058] S11. Chemically modify the aluminum nitride surface to obtain a tannic acid-modified aluminum nitride suspension. (1) Add 4 g of tannic acid (AR analytical grade) to 200 mL of anhydrous ethanol and stir until the tannic acid is completely dissolved. Add 15 g of aluminum nitride powder with a particle size of 2 microns to the prepared tannic acid ethanol solution, and then add 6 g of deionized water. (2) Place the suspension system in a stirring water bath for heating and modification, place the modified suspension in a centrifuge for centrifugal separation, add the modified and cleaned aluminum nitride powder to deionized water and disperse in an ultrasonic dispersion environment to obtain a tannic acid-modified aluminum nitride suspension.
[0059] S12. Graphene oxide is coated on the surface of modified aluminum nitride to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder. (1) 0.3 g of single-layer graphene oxide is added to 200 mL of deionized water and ultrasonically dispersed for 1 hour to obtain a graphene oxide dispersion; (2) The graphene oxide dispersion is added dropwise to the tannic acid modified aluminum nitride suspension and the mixed solution is placed in a centrifuge for centrifugal separation. The precipitated part is placed in a freeze dryer and freeze-dried for 24 hours to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder.
[0060] S13, reducing the composite particles at high temperature to obtain multilayer graphite-coated aluminum nitride ceramic powder, and placing the graphene oxide-coated aluminum nitride ceramic powder in a tubular furnace for reduction under a nitrogen atmosphere.
[0061] This embodiment also provides a method for preparing a heat-conducting and wave-absorbing gasket, and the steps are as follows:
[0062] S21, multilayer graphite coated aluminum nitride ceramic powder and aluminum nitride powder are graded to obtain multilayer graphite coated aluminum nitride graded powder. (1) The aluminum nitride particle size used for grading is 30 microns; (2) The mass ratio of the grading is 1:1.1 for the multilayer graphite coated aluminum nitride and the aluminum nitride.
[0063] S22, adding an organic crosslinking agent and a curing agent to the graded powder of multilayer graphite coated aluminum nitride, mechanically stirring, vacuuming and removing bubbles, and then standing to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry. (1) Maleic anhydride and terminal hydroxyl polybutadiene are mixed in a mass ratio of 2:1 to obtain an organic crosslinking agent; (2) 13.8g of graded aluminum nitride powder and 1.2g of organic crosslinking agent are added to a mixing tank, and then 0.75g of dodecyltrimethylsilane is added as a curing agent, and the mixture is placed in a mixer and mixed under vacuum to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry.
[0064] S23, using a tablet press to press the multi-layer graphite-coated aluminum nitride thermally conductive and absorbing slurry into a uniform sheet, and curing it in a high temperature environment to obtain a multi-layer graphite-coated aluminum nitride thermally conductive and absorbing gasket.
[0065] The basic wave absorption performance of the multilayer graphite-coated aluminum nitride ceramic powder obtained on this basis is: RLmin = -7.91dB, and the wave absorption bandwidth is 0GHz (such as Figure 3 The thermal conductivity of the gasket is 5.65W / mK (as shown). Figure 4 shown).
[0066] Example 4
[0067] This embodiment provides a method for preparing multi-layer graphite-wrapped aluminum nitride ceramic powder, the steps of which are as follows:
[0068] S11. Chemically modify the aluminum nitride surface to obtain a tannic acid-modified aluminum nitride suspension. (1) Add 6 g of tannic acid (AR analytical grade) to 200 mL of anhydrous ethanol and stir until the tannic acid is completely dissolved. Add 15 g of aluminum nitride powder with a particle size of 2 microns to the prepared tannic acid ethanol solution, and then add 6 g of deionized water. (2) Place the suspension system in a stirring water bath for heating and modification, place the modified suspension in a centrifuge for centrifugal separation, add the modified and cleaned aluminum nitride powder to deionized water and disperse in an ultrasonic dispersion environment to obtain a tannic acid-modified aluminum nitride suspension.
[0069] S12, coating graphene oxide on the surface of modified aluminum nitride to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder. (1) Add 0.75g of single-layer graphene oxide to 200mL of deionized water and disperse it ultrasonically for 1h to obtain a graphene oxide dispersion; (2) Add the graphene oxide dispersion dropwise into the tannic acid modified aluminum nitride suspension and place the mixed solution in a centrifuge for centrifugal separation. Place the precipitate in a freeze dryer and freeze-dry for 24h to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder.
[0070] S13, reducing the composite particles at high temperature to obtain multilayer graphite-coated aluminum nitride ceramic powder, and placing the graphene oxide-coated aluminum nitride ceramic powder in a tubular furnace for reduction under a nitrogen atmosphere.
[0071] This embodiment also provides a method for preparing a heat-conducting and wave-absorbing gasket, and the steps are as follows:
[0072] S21, multilayer graphite coated aluminum nitride ceramic powder and aluminum nitride powder are graded to obtain multilayer graphite coated aluminum nitride graded powder. (1) The aluminum nitride particle size used for grading is 30 microns; (2) The mass ratio of the grading is 1:1.1 for the multilayer graphite coated aluminum nitride and the aluminum nitride.
[0073] S22, adding an organic crosslinking agent and a curing agent to the graded powder of multilayer graphite coated aluminum nitride, mechanically stirring, vacuuming and removing bubbles, and then standing to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry. (1) Maleic anhydride and terminal hydroxyl polybutadiene are mixed in a mass ratio of 2:1 to obtain an organic crosslinking agent; (2) 13.5g of graded aluminum nitride powder and 1.5g of organic crosslinking agent are added to a mixing tank, and then 0.75g of dodecyltrimethylsilane is added as a curing agent, and the mixture is placed in a mixer and mixed under vacuum to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry.
[0074] S23, using a tablet press to press the multi-layer graphite-coated aluminum nitride thermally conductive and absorbing slurry into a uniform sheet, and curing it in a high temperature environment to obtain a multi-layer graphite-coated aluminum nitride thermally conductive and absorbing gasket.
[0075] The basic absorption performance of the multilayer graphite-coated aluminum nitride ceramic powder obtained on this basis is: RLmin = -56.17dB, and the absorption bandwidth is 5.2GHz. The thermal conductivity of the gasket is 4.60W / mK (such as Figure 4 shown).
[0076] Example 5
[0077] This embodiment provides a method for preparing multi-layer graphite-wrapped aluminum nitride ceramic powder, the steps of which are as follows:
[0078] S11. Chemically modify the aluminum nitride surface to obtain a tannic acid-modified aluminum nitride suspension. (1) Add 6 g of tannic acid (AR analytical grade) to 200 mL of anhydrous ethanol and stir until the tannic acid is completely dissolved. Add 15 g of aluminum nitride powder with a particle size of 2 microns to the prepared tannic acid ethanol solution, and then add 6 g of deionized water. (2) Place the suspension system in a stirring water bath for heating and modification, place the modified suspension in a centrifuge for centrifugal separation, add the modified and cleaned aluminum nitride powder to deionized water and disperse in an ultrasonic dispersion environment to obtain a tannic acid-modified aluminum nitride suspension.
[0079] S12. Coat graphene oxide on the surface of modified aluminum nitride to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder. (1) Add 0.75g of single-layer graphene oxide to 200mL of deionized water and disperse it ultrasonically for 1h to obtain a graphene oxide dispersion; (2) Add the graphene oxide dispersion dropwise into the tannic acid modified aluminum nitride suspension and place the mixed solution in a centrifuge for centrifugal separation. Place the precipitated part in a freeze dryer and freeze-dry for 24h to obtain composite particles of graphene oxide coated aluminum nitride ceramic powder;
[0080] S13, reducing the composite particles at high temperature to obtain multilayer graphite-coated aluminum nitride ceramic powder, and placing the graphene oxide-coated aluminum nitride ceramic powder in a tubular furnace for reduction under a nitrogen atmosphere.
[0081] This embodiment also provides a method for preparing a heat-conducting and wave-absorbing gasket, and the steps are as follows:
[0082] S21, multilayer graphite coated aluminum nitride ceramic powder and aluminum nitride powder are graded to obtain multilayer graphite coated aluminum nitride graded powder. (1) The aluminum nitride particle size used for grading is 30 microns; (2) The mass ratio of the grading is 1:1.1 for the multilayer graphite coated aluminum nitride and the aluminum nitride.
[0083] S22, adding an organic crosslinking agent and a curing agent to the graded powder of multilayer graphite coated aluminum nitride, mechanically stirring, vacuuming and removing bubbles, and then standing to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry. (1) Maleic anhydride and terminal hydroxyl polybutadiene are mixed in a mass ratio of 2:1 to obtain an organic crosslinking agent; (2) 13.65g of graded aluminum nitride powder and 1.35g of organic crosslinking agent are added to a mixing tank, and then 0.75g of dodecyltrimethylsilane is added as a curing agent, and the mixture is placed in a mixer and mixed under vacuum to obtain a multilayer graphite coated aluminum nitride thermal conductive wave absorbing slurry.
[0084] S23, using a tablet press to press the multi-layer graphite-coated aluminum nitride thermally conductive and absorbing slurry into a uniform sheet, and curing it in a high temperature environment to obtain a multi-layer graphite-coated aluminum nitride thermally conductive and absorbing gasket.
[0085] The basic absorption performance of the multilayer graphite-coated aluminum nitride ceramic powder obtained on this basis is: RLmin = -56.17dB, and the absorption bandwidth is 5.2GHz. The thermal conductivity of the gasket is 5.04W / mK (such as Figure 4 shown).
[0086] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing multi-layer graphite-coated aluminum nitride ceramic powder, characterized in that: The following steps are involved: S11, chemically modifying the surface of aluminum nitride by using tannic acid to prepare tannic acid-modified aluminum nitride powder with surface activity, and adding the powder into deionized water for ultrasonic dispersion to obtain a tannic acid-modified aluminum nitride suspension; S12, coating the surface of modified aluminum nitride with graphene oxide, adding graphene oxide to a deionized water solution for ultrasonic dispersion to obtain a graphene oxide dispersion, dripping the graphene oxide dispersion into the nicotinic acid-modified aluminum nitride suspension obtained in step S11 while stirring, centrifuging after the dripping, and drying to obtain composite particles of composite particles of graphene oxide-coated aluminum nitride ceramic powder; S13, placing the composite particles obtained in step S12 in a high-temperature furnace for high-temperature reduction in a protective gas environment, reducing the graphene oxide on the surface into graphene and carbonizing the tannic acid into amorphous carbon by high temperature, and obtaining a multilayer graphite-coated aluminum nitride ceramic powder.
2. The method for preparing a multi-layer graphite-coated aluminum nitride ceramic powder according to claim 1, characterized in that: The specific operation method of chemically modifying the aluminum nitride surface with tannic acid in S11 is: dissolving tannic acid in anhydrous ethanol, adding aluminum nitride powder and deionized water, ultrasonically dispersing, and then stirring and heating in a water bath environment; Among them, the mass ratio of the aluminum nitride powder to tannic acid is 1:0.4-0.5, the mass volume ratio of the aluminum nitride powder, anhydrous ethanol and deionized water is 1g:12-13mL:0.4g; the ultrasonic dispersion time is 30-60min; the water bath temperature is 75-80°C, the stirring speed is 500-600rpm, and the stirring and heating time in the water bath environment is 210-300min.
3. The method for preparing a multi-layer graphite-coated aluminum nitride ceramic powder according to claim 2, characterized in that: In step S12, the mass ratio of modified aluminum nitride to graphene oxide is 20 to 50:1; The ultrasonic dispersion time of the graphene oxide in the deionized water solution is 30 to 60 minutes; the stirring speed is 400 to 600 rpm; the centrifugal parameter is 4000 rpm for 4 minutes, repeated four times; and the drying method is freeze drying for 24 to 48 hours.
4. The method for preparing a multi-layer graphite-coated aluminum nitride ceramic powder according to claim 3, characterized in that: In step S13, the graphene oxide-coated aluminum nitride ceramic powder is reduced at a high temperature of 800 to 850° C. for 4.5 to 5.5 hours in a nitrogen environment, and then cooled to room temperature in the furnace.
5. A method for preparing a thermally conductive wave-absorbing gasket, characterized in that: The following steps are involved: S21, grading the multilayer graphite-coated aluminum nitride ceramic powder obtained by the preparation method according to any one of claims 1 to 4 with aluminum nitride powder to obtain a multilayer graphite-coated aluminum nitride graded powder; S22, adding an organic crosslinking agent and a curing agent to the multi-layer graphite-coated aluminum nitride graded powder, mechanically stirring, vacuuming and removing bubbles, and then standing to obtain a multi-layer graphite-coated aluminum nitride thermal conductive and wave absorbing slurry; S23, using a tablet press to press the multi-layer graphite-coated aluminum nitride thermally conductive and absorbing slurry into a uniform sheet, and curing it in a high temperature environment to obtain a multi-layer graphite-coated aluminum nitride thermally conductive and absorbing gasket.
6. The method for preparing a heat-conducting and wave-absorbing gasket according to claim 5, characterized in that: In step S21, the particle size of the aluminum nitride powder is 30-35 μm.
7. The method for preparing a heat-conducting and wave-absorbing gasket according to claim 5, characterized in that: In the step S21, the gradation mass ratio of the multilayer graphite-coated aluminum nitride ceramic powder to the aluminum nitride powder is 1:0.5-2.
8. The method for preparing a heat-conducting and wave-absorbing gasket according to claim 5, characterized in that: In step S22, the organic crosslinking agent comprises maleic anhydride and hydroxyl-terminated polybutadiene, and the mass ratio of maleic anhydride to hydroxyl-terminated polybutadiene is 1:0.5; The curing agent is dodecyltrimethylsilane, and the content of the curing agent is 0.5% of the total mass of the multi-layer graphite-coated aluminum nitride thermal conductive wave absorbing slurry.
9. The method for preparing a heat-conducting and wave-absorbing gasket according to claim 5, characterized in that: In the step S22, the mass ratio of the multilayer graphite-coated aluminum nitride graded powder to the organic cross-linking agent is 1:0.2-0.
08.
10. The method for preparing a heat-conducting and wave-absorbing gasket according to claim 5, characterized in that: In the step S23, the multi-layer graphite-coated aluminum nitride heat-conducting and wave-absorbing gasket is pressed to a thickness of 1 mm to 3 mm, the curing temperature is 120° C., and the curing time is 2 to 3 hours.
Citation Information
Patent Citations
Graphene coated alumina ceramic powder as well as preparation method and application thereof
CN107353017A
High heat conductivity insulating graphene / alumina / aluminum composite material and preparation method thereof
CN109942296A
Polymer composite material based on aromatic compound modified heat-conducting insulating composite powder and preparation of polymer composite material
CN114806081A
Shell, preparation method thereof and electronic equipment
CN115604943A
High-thermal-conductivity carbide or nitride spherical powder with core-shell structure and preparation method of high-thermal-conductivity carbide or nitride spherical powder
CN117401981A
